PENGARUH PESAN IKLAN DAN PRSEPSI KUALITAS TERHADAP NIAT BELI PRODUK ASUS ZENFONE 3 MAX (Studi pada Pengujung WTC Surabaya) - ISNANI Z.N, INA (Jurnal Ilmu Manajemen (JIM), 2017)
The rise of the technology and information bring a big impact to people. One of them , are the smartphone products. Demand of the bigger smartphone product, becomes an opportunity for manufacture as Asus to sell their products. Had occupying the position of the crest on the market smartphone in Indonesia, Asus losing market . So, Asus roll out the leading product, Asus ZenFone 3 max. In order to controlling market back , Asus trying to understand behavior of their consumer with a focus on issues capable of effecting purchase intentions , which advertising message and consumen’s perceive of quality. The kind of this reseach is quantitative. The population of this reseach were World Trade Center Surabaya visitors aged 18-50 years, that have not smartphone product Asus ZenFone 3 Max, the total of sampel were 110 respondents. Sampling technique used non-probability sampling and usesd incidental sampling technique. The scale of measurenment used Likert scale. The statistics analyze used multiple regression with BM SPSS Statistics 20 program. The result shows that have effect of advertising message and perceive of quality on purchase intentions. Based of the result t test showed that advertising message variable and perceive of quality variable have influence on purchase intentions and have positive relationship. Keywords: advertising message, perceive quality, purchase intention